Sexual harassment: is it a case of gendered perspective? - Kenny, Kamal; Abu Samah, Asnarulkhadi; Chan, Benjamin Yin Fah (Center for Promoting Ideas, 2011)
Globally, the phenomenon of Sexual harassment has always been looked from a woman’s perspective. To date, almost all studies on sexual harassment look at the incidences of sexual harassment, the effects on victims and coping strategies for victims; and in most instances victims are women. There is a dire need to change our understanding of this issue. In order to obtain a more holistic view of this issue, there should be a paradigm shift where the focus should be on the perpetrators. As men are generally the perpetrators, it is about time the phenomenon of sexual harassment is looked from a male perspective in understanding what brought men to engage in the act of sexual harassment.